The Effect of Lactation on Post‐Partum Uterine Involution in Holstein Dairy Cows. Issue 6 (21st May 2013) - Scully, S; Maillo, V; Duffy, P; Kelly, AK; Crowe, MA; Rizos, D; Lonergan, P
Contents: The objective was to examine the effect of lactation on uterine involution in post‐partum dairy cows. Holstein primiparous cows were used (n = 19, mean age: 3.9 ± 0.1 years). At calving, cows were randomly assigned to one of two treatment groups, lactating (n = 11) or non‐lactating (i.e. dried off at calving, n = 8). Examination of the reproductive tract was carried out by ultrasonography twice weekly until week 7 post‐partum. Blood samples were collected twice weekly for the analysis of progesterone to indicate the resumption of cyclicity and metabolites indicative of energy status. Uterine involution was assessed in terms of size of the uterine horns, uterine body diameter and uterine fluid volume as assessed by the amount of non‐echogenic material measured by ultrasound and position of the uterus. Vaginal mucous score was taken on day 28 post‐partum for the assessment of uterine inflammation. Resumption of cyclicity (serum progesterone > 1 ng/ml) had occurred in both groups on average by day 21 post‐partum. Concentrations of non‐esterified fatty acids and beta‐hydroxybutyrate were higher, whereas concentrations of glucose, insulin and IGF‐1 were lower (p < 0.05) in lactating compared to non‐lactating cows. Lactating cows had a smaller mean uterine body diameter (p < 0.05) than non‐lactating cows from days 28 to 42 post‐partum (day 28: 20.2 ± 1.3 vs 24.9 ± 1.5 mm, respectively) and had a lower mean uterine fluid volume up to day 49 (p < 0.05). By day 49, there was no difference in uterine diameter (15.2 ± 1.8 vs 15.2 ± 1.6 mm) or uterine fluid volume (0.11 ± 0.38 vs 0.18 ± 0.46) between lactating and non‐lactating cows, respectively. Vaginal mucous score revealed no evidence of uterine inflammation in either group. In conclusion, while lactation induced significant alterations in metabolic status, it did not have a major effect on the rate of uterine involution as defined in this study.